Severe infections in patients with lymphoproliferative diseases treated with new targeted drugs: A multicentric real‐world study. (23rd September 2021) - Stefania Infante, Maria; Fernández‐Cruz, Ana; Núñez, Lucia; Carpio, Cecilia; Jiménez‐Ubieto, Ana; López‐Jiménez, Javier; Vásquez, Lourdes; Del Campo, Raquel; Romero, Samuel; Alonso, Carmen; Morillo, Daniel; Prat, Margarita; et al.
Abstract: Background: Lymphoid neoplasms treatment has recently been renewed to increase antitumor efficacy and conventional chemotherapies toxicities. Limited data have been published about the infection risk associated with these new drugs, therefore this study analyzes the infectious complications in patients with lymphoproliferative diseases (LPD) treated with monoclonal antibodies (obinutuzumab, ofatumumab, brentuximab, nivolumab, or pembrolizumab), BTK inhibitors (ibrutinib and acalabrutinib), PI3K inhibitors (idelalisib) and BCL2 inhibitors (venetoclax). Methods: Multicenter retrospective study of 458 LPD patients treated with targeted therapies in real‐life setting, in 18 Spanish institutions, from the time of their commercial availability to August 2020. Results: Severe infections incidence was 23% during 17‐month median follow‐up; cumulative incidence was higher in the first 3–6 months of targeted drug treatment and then decreased. The most frequent etiology was bacterial (54%). Nine (6%) Invasive fungal infections (IFI) were observed, in its majority in chronic lymphocytic leukemia (CLL) patients treated predominantly with ibrutinib. Significant risk factors for severe infection were: severe lymphopenia ( p = 0.009, OR 4.7, range 1.3–1.7), combined targeted treatment vs single agent treatment ( p = 0.014 OR 2.2 range 1.1–4.2) and previous rituximab ( p = 0.03 OR 1.8, range 1.05–3.3). Infection‐related mortality was 6%. In 22% of patients with severe infections, definitive discontinuation of the targeted drug was observed. Conclusion: A high proportion of patients presented severe infections during follow‐up, with non‐negligible attributable mortality, but infection incidence is not superior to the one observed during the chemotherapy era. In selected cases with specific risk factors for infection, antimicrobial prophylaxis should be considered. Abstract : Our data describe the infection risk associated with the use of targeted drugs in the treatment of lymphoproliferative diseases in real‐life setting and suggest some infection risk factors that could identify the need for antimicrobial prophylaxis in a selected group of patients.